Creating pathways 2005 National Indigenous Dance Forum : [Report]. - Miller, Lydia; Blanco, Raymond, 1961-; Dyson, Julie, 1944-; Jennings, Rachel; Morrow, Wendy; Stevens, Monica, 1962- ([Sydney] : Australia Council for the Arts, 2005)
Report from the 2005 Creating Pathways Forum (27 - 30th October 2005) at National Museum, Canberra; Indigenous dance practitioners exploring a collective vision and direction for Indigenous dance; funded by the Aboriginal and Torres Strait Islander Arts Board and Dance Board of Australia Council; organised by Ausdance National.
Event overview, keynote speech, reflection, creating pathways program, Ausdance report, paths for action, participants list.
Title from document (viewed 07 feb 2008)
Text.
System requirements: PDF reader required to read document
Selected for archiving
Keywords: Choreographers -- Australia; Dance -- Study and teaching; Dance, Aboriginal Australian; Dance - Education; Performing arts - Ballet and modern dance; Performing arts - Dance companies; Performing arts - Training and workshops